PENGARUH KUALITAS PRODUK, ATMOSFER DAN LOKASI TERHADAP KEPUASAN PELANGGAN DI THE CAFE HOTEL MULIA SENAYAN - Rully Arifiansyah; Melina Aulia; Agus Riyanto (Panorama Nusantara, 2020)
Business competition in restaurants is growing, so restaurants are required to not only focus on their sales targets, in order to survive in the midst of intense competition. The purpose of this study is to measure customer satisfaction at THE CAFÉ Hotel Mulia Senayan. By testing several variables including food quality, atmosphere, and location. The methodology of this research uses quantitative analysis of multiple linear regression using IBM SPSS (Statistical Package for Social Science) software. This study uses purposive sampling techniques to customers by distributing questionnaires. The results showed that food quality, atmosphere, and location simultaneously and partially affected customer satisfaction.